É possível produzir variabilidade em metacontingências? - Santos, Priscila Martins dos (2011)
This study aimed to investigate if it was possible to produce variability in metacontingencies or better, in the aggregate products produced by interlocking contingencies. Two experiments were conducted in which undergraduate students distributed in generations or three participants worked simultaneously. In each generation change the oldest participant in experimental setting was replaced by a naïve participant. The task to each participant, in a computer screen, was to insert 4 numbers from 0 to 9 below 4 numbers presented by the software (also from 0 to 9). Credits (exchanged by money at the end of experiment) could be obtained through points and/or bonuses. Points were individual consequences produced when the sum of numbers presented by the software and those inserted by the participant, in each column, resulted in an odd number in the 4 columns. Bonuses were cultural consequences, obtained when the sum of the 4 numbers inserted by the participant on the left lineage (LE) were smaller than the sum of the numbers inserted by the participant on the central lineage (LC), which was smaller than the sum of the numbers of the participant on the right lineage (LD) producing the aggregate product SLE < SLC < SLD. Experiment 1 had 14 participants (12 generations) and investigated if the removal of a correction procedure used in other researches could promote more variability than that produced in those studies. It was found that this manipulation was not enough to produce variability, and the results were quite similar to the ones from the earlier studies. It was, then, conducted the Experiment 2, also having 14 participants (12 generations) which investigated if a participants reallocation procedure, in each generation change, could produce more variability than it was produced before. It was found to occur more variability in comparison to the other studies, but some variability reduction was also observed (still less drastic than that from Experiment 1), which seems to be typical of selection of / by metacontingencies. The first verbal interactions every generation change were also analyzed in both experiments. The results of this analysis sustained the other results obtained and denoted again to having had differences between the conducted experiments. Other studies are suggested, in order to investigate other aspects involved in the correlation between variability and metacontingencies. Finally, this study corroborate the findings from previous studies and once again and shows that this research protocol enables to investigate different aspects involved in selection of / by metacontingencies